Ruptured Pseudoaneurysm of a Brachiocephalic Arteriovenous Fistula: A Case Report - Jeffrey Surya; Prasetyo Edi (CV. Jasa Sukses Abadi, 2026)
Pseudoaneurysm is a vascular abnormality caused by disruption of the arterial wall, resulting in the extraluminal accumulation of blood within a sac-like cavity. This condition may arise from infection, inflammation, trauma, or iatrogenic causes that may progressively enlarge, compress surrounding neurovascular structures, and eventually rupture, leading to active bleeding. Hemorrhage from an arteriovenous fistula is an uncommon but potentially life-threatening emergency. Therefore, prompt surgical management is essential to prevent limb ischemia and reduce mortality. We report the case of a 32-year-old man who presented with acute bleeding, swelling, and pulsatile pain in the left arm two hours prior to admission. The limb had undergone brachiocephalic arteriovenous fistula creation two weeks earlier. Physical examination revealed swelling, purulent discharge, and blood clots at the surgical site, consistent with a ruptured pseudoaneurysm. Initial management in the emergency department included direct compression, intravenous fluid resuscitation, and antifibrinolytic therapy. The patient subsequently underwent emergency vascular reconstruction. Intraoperative findings showed complete rupture of the cephalic vein, which was not salvageable. The brachial artery, however, had a subtotal rupture and was preserved. A side-to-side vein patch plasty using the great saphenous vein was performed. The patient demonstrated clinical improvement postoperatively and was discharged after three days. At the two-week follow-up, no complications were noted, particularly signs of distal limb ischemia.